Integrative Genome-Wide DNA Methylome and Transcriptome Analysis of Ovaries from Hu Sheep with High and Low Prolific - Yao, Xiaolei; Li, Fengzhe; Wei, Zongyou; EI-Samahy, M. A.; Feng, Xu; Yang, Fan; Wang, Feng (Frontiers in Cell and Developmental Biology, 2022)
DNA methylation plays an important role in biological processes by affecting gene expression. However, how DNA methylation regulates phenotypic variation in Hu sheep remains unclear. Therefore, we generated genome-wide DNA methylation and transcriptomic profiles in the ovaries of Hu sheep with different prolificacies and genotypes (FecBB and FecB+). Results showed that ovary DNA methylome and transcriptome were significantly different between high prolificacy and low prolificacy Hu sheep. Comparative methylome analyses identified 10,644, 9,594, and 12,214 differentially methylated regions and 87, 1,121 and 2,375 genes, respectively, showing differential expression levels in three different comparison groups. Female reproduction-associated differentially methylated regions-related genes and differentially expressed genes were enriched, thereby the respective interaction networks were constructed. Furthermore, systematical integrative analyses revealed a negative correlation between DNA methylation around the transcriptional start site and gene expression levels, which was confirmed by testing the expression of integrin β2 subunit (ITGB2) and lysosome-associated protein transmembrane-4 beta (LAPTM4B) in vivo and in vitro. These findings demonstrated that DNA methylation influences the propensity for prolificacy by affecting gene expression in the ovaries, which may contribute to a greater understanding of the epigenome and transcriptome that will be useful for animal breeding.